Pemanfaatan E-Customer Relationship Management untuk Peningkatan Usaha Tour & Travel dengan Pengujian User Centered Design - Yanto, Widja; Mulyono, Herry (Forum Kerjasama Pendidikan Tinggi (FKPT), 2024)
Nada Salwa Tour & Travel is one of the service businesses operating in the travel sector. Currently, the existing system faces challenges in acquiring new customers, enhancing relationships with existing ones, and retaining them. To address these issues, Nada Salwa Tour & Travel requires a web-based Electronic Customer Relationship Management (E-CRM) system that can assist both the company and its customers in fostering good relationships. The objective of this research is to analyze the service relationship between the company and its customers and to design a Sistem web-based Electronic Customer Relationship Management (E-CRM) system to create better relationships through website features. The author conducted object-oriented design including Use Case diagrams, activity diagrams, class diagrams, interface designs, and database structure tables. The result of this research is a Sistem web-based E-CRM system that can help address the existing problems at Nada Salwa Tour & Travel. The testing result of the designed interface using the cognitive walkthrough method with 5 respondents shows learnability at 96.15%, error rate at 1.34%, and efficiency at 94.93%.